Narratives - Peters, Christopher Thomas (The Trumpeter, 2022)
We are caught just now between acting in the face of an overwhelming environmental collapse, and trying to understand where to begin. How do we educate for this new reality? What are the stories that need telling, now? The answer, of course, isn't found in technological marvels or bio-engineering. To know the world, this place - the northeast Avalon Peninsula, attached to Newfoundland proper by a narrow isthmus - we have to be in it. We’ll take the sleet and the rain, the howling winds and the sudden downpours. We’ll take the swirl of May fogs, with the mercury struggling to break five degrees Celsius, that last for days like weeks. We need the mundane. The mundane defines us. It brings people together. It grounds us in stories that speak back years and generations, all rooted here.